Parasitaemia pattern and mortality of mice infected by Indonesian Isolate of Trypanosoma evansi. - Didik T. Subekti; Sawitri DH; Wardhana AH; Suhardono . (Indonesian Center for Animal Research and Development (ICARD), 2013)
Trypanosomiasis (Surra) is one of the parasitic diseases is endemic and deadly for horses and buffalo in Indonesia.The etiology of the disease is a Trypanosoma evansi. Some T. evansi isolates had been isolated and cryopreservated. Those isolates had not been studied for their differences in virulence, particularly with regard to the pattern of parasiteaemia and their ability to promote mice mortality. Therefore in this study the differences in virulence was studied. DDY mice were divided in to 19 groups according to each isolate to be tested. Each group consisted of 5 mice. Infection were carried intraperitoneally at a dose of 104 Trypanosoma/mice. Mice were examined every two days. Blood samples were taken from tail’s peripheral blood and were examined under light microscope. Parasite were quantitatively counted using Naubauer chamber. Parasitemia and mice survival were observed for 30 days or until all mice died.The results indicated that there was significant difference among the isolates.Through out the nineteenth isolate scan could be grouped into 3 different biotypes associated with patterns of parasitemia and their ability to kill mice. Biotype1 was the most virulent with the ability to promote mice mortality ≤ 8 days post-infection (dpi). The biotype2 and 3 were the lowest compared to biotype 1. Biotype2 had an undulating parasitaemia, where as biotype 3 showed persistently high parasitaemia with the ability to promote mice mortality ≥ 14dpi. The results also indicate the presence of mixed infections of biotypes that exist in one isolate of T. evansi. Key Words: Trypanosoma evansi, Biotype, Virulence, Mixed infection, Parasitaemia